OsHYPK-mediated protein N-terminal acetylation coordinates plant development and abiotic stress responses in rice - Gong, Xiaodi; Huang, Yaqian; Liang, Yan; Yuan, Yundong; Liu, Yuhao; Han, Tongwen; Li, Shujia; Gao, Hengbin; Lv, Bo; Huang, Xiahe; Linster, Eric; Wang, Yingchun; et al. (Molecular plant, 2022)
N-terminal acetylation is one of the most common protein modifications in eukaryotes, and approximately 40% of human and plant proteomes are acetylated by ribosome-associated N-terminal acetyltransferase A (NatA) in a co-translational manner. However, the in vivo regulatory mechanism of NatA and the global impact of NatA-mediated N-terminal acetylation on protein fate remain unclear. Here, we identify Huntingtin Yeast partner K (HYPK), an evolutionarily conserved chaperone-like protein, as a positive regulator of NatA activity in rice. We found that loss of OsHYPK function leads to developmental defects in rice plant architecture but increased resistance to abiotic stresses, attributable to perturbation of the N-terminal acetylome and accelerated global protein turnover. Furthermore, we demonstrated that OsHYPK is also a substrate of NatA and that N-terminal acetylation of OsHYPK promotes its own degradation, probably through the Ac/N-degron pathway, which could be induced by abiotic stresses. Taken together, our findings suggest that the OsHYPK-NatA complex plays a critical role in coordinating plant development and stress responses by dynamically regulating NatA-mediated N-terminal acetylation and global protein turnover, which are essential for maintaining adaptive phenotypic plasticity in rice.
Gesehen am 07.07.2022